Maqāṣid Al-Sharīʿah Based Comparative Analysis Of Crypto Asset Regulation In Indonesia, Malaysia, And The United Arab Emirates - Farrel Izham Prayitno; Ahmad Multazam (Muhammadiyah University of Surabaya, 2026)
The rapid expansion of crypto assets since 2020 has generated complex challenges for Islamic economic law, particularly regarding the coherence of legal norms and fatwas across jurisdictions. Although crypto assets offer economic opportunities, regulatory and juristic responses in Muslim majority countries remain fragmented, reflecting the absence of a standardized maqāṣid al sharīʿah based evaluative framework. This study aims to analyze and compare the legal norms and fatwas governing crypto assets in Indonesia, Malaysia, and the United Arab Emirates during 2020 to 2025 from a maqāṣid-oriented perspective. The research employed a normative comparative legal approach supported by an evaluative simulation model, utilizing secondary data from publicly available regulations, fatwas, and official policy documents. The simulation operationalized key maqāṣid dimensions, namely protection of wealth, protection of intellect, and prevention of harm, across three regulatory scenarios consisting of crypto assets as means of payment, commodities or investment instruments, and objects of zakat. The results show that crypto assets receive higher normative acceptance when positioned as commodities or investment instruments, while their treatment as means of payment and zakat objects remains legally contested. Cross-jurisdictional variations reveal how differing institutional priorities and implicit maqāṣid orientations shape regulatory outcomes. These findings contribute theoretically by demonstrating the applicability of maqāṣid al sharīʿah as an operational evaluative tool in digital finance governance and practically by offering a framework to support the harmonization of fatwas and regulatory policies. Overall, the study highlights the importance of a standardized maqāṣid based approach to enhance legal coherence and certainty in regulating crypto assets within Islamic economic systems. Keywords: Maqāṣid Al-Sharīʿah, Crypto Assets, Legal Norms And Fatwas, Islamic Economic Law, Comparative Legal Analysis.